2020
DOI: 10.1080/17405629.2020.1764842
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorder symptomatology in Belgian emerging adults: Associations with identity processes and statuses

Abstract: Individual differences in identity development are commonly captured by identity statuses, representing combinations of high and/or low scores on identity exploration and commitme nt processes. Although identity impairment is considered a potential diagnostic criterion of all personality disorders (PDs) in Section III of DSM-5, studies that relate identity processes or statuses to PDs are limited. The current study examined associations between identity processes and statuses, and dimensionally measured PDs am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Consistently with studies focused on other identity domains (Bogaerts et al, 2021), mothers with higher borderline and depressive symptoms turned out to be at higher risk for lower commitment and identification with a parental role, stronger doubts about being a parent, and dreaming about the 'life without kids' (Piotrowski, 2021b). The present study, like an earlier study by Meca et al (2020) on a sample of U.S. parents, also confirmed that the dimension of exploration is not closely related to parents' mental health.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistently with studies focused on other identity domains (Bogaerts et al, 2021), mothers with higher borderline and depressive symptoms turned out to be at higher risk for lower commitment and identification with a parental role, stronger doubts about being a parent, and dreaming about the 'life without kids' (Piotrowski, 2021b). The present study, like an earlier study by Meca et al (2020) on a sample of U.S. parents, also confirmed that the dimension of exploration is not closely related to parents' mental health.…”
Section: Discussionsupporting
confidence: 88%
“…Among its different correlates, depressive and anxiety symptoms are also closely related to personality pathology such as borderline personality disorder (BPD; Gunderson and Philips, 1991 ; Koenigsberg et al, 1999 ), which has not yet been studied in the context of parental identity. People with BPD, experience highly unstable emotional and relational life, are characterized by strong and unpredictable reactions, risky behaviors, unstable self-esteem and also a fragile sense of identity ( Gunderson and Philips, 1991 ; Bogaerts et al, 2021 ). Thus, it can be assumed that parents with high borderline symptoms may also have considerable difficulty forming a stable identity of themselves as parents.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the present findings could be explained by a spectrum/continuity model, in which identity and substance use might be extremities of the same underlying construct, or a common cause model. While the former seems unlikely, in the latter case, both identity issues and substance use may, for instance, be predicted by stressful experiences (Anthis, 2002;Low et al, 2012), personality pathology (Bogaerts et al, 2020), or lack of autonomy (Ryan et al, 2006). However, several issues need to be considered before we can apply these explanations.…”
Section: Identity and Substance Usementioning
confidence: 99%
“…As of April 2022, the original manuscripts about the U-MICS (Crocetti et al, 2008) and the DIDS (Luyckx et al, 2008) have been cited more than 350 and 430 times in Web of Science and over 750 and 990 times in Google Scholar, respectively. The wide use of these measures reflects the high relevance of these processes for myriad aspects of both adaptive and maladaptive functioning across the lifespan for both clinical (e.g., Klimstra & Denissen, 2017) and general (Bogaerts et al, 2021) applications.…”
Section: The Current Analysesmentioning
confidence: 99%